The Hebephiliac: Pedophile or Teleiophiliac? - Sea, Jonghan (International journal of offender therapy and comparative criminology, 2018)
The current study aims to fill the gap on hebephile sex offenders by comparing them to a group of pedophile offenders as well as a group of teleiophile offenders. The focus of the study is to examine the victims’ and offenders’ characteristics, the crime characteristics, and the modus operandi used by a sample of 111 male sex assaults currently serving a sentence for sexual crimes in Korea. Looking at all the comparisons conducted, it seems that the hebephiliac is not more similar to the pedophile nor the teleiophiliac. He is in fact a mix of both. Aside from certain characteristics that make hebephiliacs different from the other two subtypes of sex offenders (e.g., sadism, travelling longer than 2 km to commit the crime, history of bipolar disorder), they mainly share characteristics of both groups. The current study uncovers very important differences that could prove useful for the management of these cases by the actors of the criminal justice system.